Pakistan : Founder's Aspirations and Today's Realities - Edited by Hafeez Malik (Karachi Oxford University Press, 2001)
Pakistan and Pakistan's public figures are assessed in this analysis of the political processes, the role of the judiciary, the executive, economic development and the role of foreign policy.
Include Index
Keywords: Pakistan movement -- Pakistan -- Politics and government -- Pakistan -- History